A case of generalised cutaneous apocrine cystomatosis in a Pekingese dog. Issue 2 (8th February 2022) - Stazi, Marica; Silvestri, Serenella; Mechelli, Luca; Brachelente, Chiara
Abstract: Clinical, histological and immunohistochemical examination of a 13‐year‐old male client‐owned Pekingese dog revealed an uncommon presentation of apocrine cutaneous cystomatosis. This is a rare non‐neoplastic condition of uncertain cause, characterised by multiple cystically dilated apocrine sweat glands. We aimed to describe the features of this unusual case of generalised cutaneous apocrine cystomatosis in the dog, which can be useful to distinguish it from multifocal benign cystic apocrine tumours. Abstract : Clinical, histological, and immunohistochemical description of an uncommon case of generalised cutaneous apocrine cystomatosis in a Pekingese dog.